INVESTIGATION OF THE LIPID, PHOSPHOLIPID, FATTY ACID AND PHOSPHATIDYLCHOLINE CONTENT AND COMPOSITION OF THE VIETNAMESE SOFT CORAL CAPNELLA SP. - Phuong Ly, Dang Thi; De, Tran Quang; Quan, Pham Minh; Kim Hoa, Dinh Thi; Theu, Nguyen Thi; Hai Linh, Luu Thi; Long, Pham Quoc; Borisovich, Andrey Imbs (Vietnam Journal of Marine Science and Technology, 2016)
The total lipid content of the soft coral Capnella sp. contained 1.44 ± 0.10% of the fresh weight. In the fatty acid content, the tetracosapolyenoic fatty acids 24:5n-6 and 24:6n-3, which were the typical markers for the soft corals (the eight compartment coral), and the fatty acids that marked for symbiotic microorganism including 18:5n-3, 18:2n-6, 18:3n-6, 18:4n-3, 20:4n-3 were presented. The result of the lipid composition analysis showed that the total lipid contained polar lipid, sterol, free fatty acid, triacylglycerol, monoalkyldiacylglycerol, hydrocarbon and wax. Of these, the polar lipid displayed the highest content with 21.14 ± 1.17% of the total lipid. The phospholipid composition of the soft coral Capnella sp. contained the characteristic phospholipid subclasses of the animals of the phylum Cnidaria, including phosphatidylethanolamine, phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and ceramide aminoethylphosphonate (phosphonolipid, CAEP). Of these, phosphatidylcholine exhibited the highest content with 35.53 ± 1.46% of the total phospholipid. This is the first time that the content and composition of the molecular types of the phosphatidylcholine from a Vietnamese soft coral species have been investigated and reported. By using modern mass spectrometry IT TOF LC-MS, the presence of 13 molecular types have been precisely identified, which PC 18:0e/20:4 and PC 16:0e/20:4 were the two ingredients displaying the highest content.